Tanggung Jawab Hukum Pelaku Usaha terhadap Produk Cacat yang Merugikan Konsumen - Cahlia; Marni (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the legal liability of business actors for defective products that harm consumers based on Law Number 8 of 1999 concerning Consumer Protection. This study also aims to identify the forms of business actor liability, analyze the dispute resolution mechanisms available to consumers, identify the inhibiting factors in the implementation of business actor liability, and formulate efforts to improve the effectiveness of legal protection for consumers in the future. This study uses normative legal research method with statute approach and conceptual approach, through literature study on primary, secondary, and tertiary legal materials. The results show that the regulation of business actor liability has been comprehensively regulated in the law by adopting the principle of strict liability. Forms of liability include material, administrative, and criminal compensation. Dispute resolution mechanisms can be pursued through litigation and non-litigation channels. However, its implementation still faces juridical, sociological, and economic obstacles. Efforts to improve effectiveness require regulatory refinement, institutional strengthening, public education, and the development of adaptive alternative dispute resolution mechanisms.